Optimization of mini-CHP under variable operating conditions - Lola A. Nizamova; Romen A. Zakhidov; Saodat R. Axmatova (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: this article discusses the use of advanced technology for generating thermal and electrical energy using the cogeneration method. Given the known schedules of thermal and electrical energy consumption, the tasks are: select a mini-CHP of the required power, optimize its connection diagram and circuit elements, calculate the cost of the resulting thermal and electrical energy and evaluate the efficiency of the investment. The creation of generating capacities with technology that makes it possible to obtain cheap electricity from existing heat consumption will create competition among electricity suppliers and will serve as a restraining factor for tariff growth. Aim: analysis of the impact on thermal efficiency indicators and operating parameters of the level of design heat loads, the composition of the main equipment of the station, technical characteristics of gas turbine units, seasonal changes in the current ambient air temperature. Methods: thermodynamic analysis methods were used during development. When optimizing the parameters of a mini-CHP, the system of compiled equations was differentiated. Results: the calculations of the options confirmed the conclusion that gas turbine-CHP plants with less powerful and economical gas turbines can have greater annual efficiency, that is, when choosing the composition of the main equipment, the selection of the standard size of the gas turbines used should be given serious attention.